Perfil cardiorrespiratório entre atacantes e defensores deuma equipe profissional de rugby - Montero, E. R.; Mendes, A.; Paz, G. A.; Miranda, H. L.; Lima, V. P. (Revista Brasileira de Ciência e Movimento, 2016)
Rugby is characterized for a competitive sport usually played by 15 subjects on each team. It is a sport that requires the extreme physical skills, containing short running at high speeds, physical collisions between athletes and great muscle power (muscle power). The Yo-yo test consists on execute out intermittent exercise performed progressively increasing speed, active rest with 10 seconds and executed until the subject was exhausted, designed to evaluate aerobic profile. This study aimed to assess by testing protocol yoyo level one VO2 maximum rugby players in the metropolitan region of Rio de Janeiro city. The study included 25 male players aged 24.16 ± 6.35 years, body mass 80 ± 9.2 kg, height 1.79 ± 5.6M. All reviews conducted three sessions of Yo Yo test level 1 with an interval of 72 hours between sessions getting an average for the group of 45.25 ± 3.8 ml*kg*min-1 to VO2 max kg.min, and 47. ml*kg*min-1 for forwards (defenders) and 42.3 ml*kg*min-1 to Backs (attackers). In the descriptive analysis the mean and standard deviation of the variables were calculated. The Shapiro-Wilk test determined that the data are parametric the paired t test was used to compare the average distance andVO2 Max estimated in the yo-yo test between defenders and attackers. Statistical analysis was performed using SPSS 20.0 software and for all analyzes was adopted p value <0.05. Found that forwards group, although their bigger body mass and stature, had a better aerobic profile when compared to the backs groups. When analyzing the total distance traveled after the test was higher in the group of defenders.